A fluorescent molecular rotor for the in situ imaging of latent fingerprints. Issue 51 (22nd November 2022) - Choi, Na-Eun; Kim, Eun-Ji; Lee, Jiyoun
Abstract : We developed a fluorescent molecular rotor that responds to hydrophobic and viscous environments and visualizes latent fingerprints with level 3 details. Abstract : Efficient techniques for developing latent fingerprints are invaluable resources to solve crimes. In this work, we developed a fluorescent molecular rotor probe that responds to hydrophobic and viscous environments and visualizes latent fingerprints with level 3 details. We believe that the simple and convenient features of LFP-1 will benefit forensic practice.